Differentiability of Solutions of Abstract Neutral Integro-Differential Equations - Henriquez-Miranda, H (2013)
In this paper we study the differentiability of solutions of abstract neutral integro-differential equations with infinite delay. We consider specially the cases when the underlying space is reflexive or at least has the Radon- Nikodym property. © 2013 Rocky Mountain Mathematics Consortium.